The Effects of Tai Chi on Cardiovascular Risk in Women - Robins, Jo Lynne; Elswick, R. K.; Sturgill, Jamie; McCain, Nancy L. (American journal of health promotion, 2016)
Purpose. This study examined the effects of tai chi (TC) on biobehavioral factors associated with cardiovascular disease (CVD) risk in women. Design. A randomized trial used a wait-list control group, pretest-posttest design. Data were collected immediately before, immediately after, and 2 months following the intervention. Setting. The study was community based in central Virginia. Subjects. Women aged 35 to 50 years at increased risk for CVD. Intervention. The 8-week intervention built on prior work and was designed to impact biobehavioral factors associated with CVD risk in women. Measures. Biological measures included fasting glucose, insulin, and lipids as well as C-reactive protein and cytokines. Behavioral measures included fatigue, perceived stress, depressive symptoms, social support, mindfulness, self-compassion, and spiritual thoughts and behaviors. Analysis. A mixed effects linear model was used to test for differences between groups across time. Results. In 63 women, TC was shown to decrease fatigue (∂ [difference in group means] = 9.38, p = .001) and granulocyte colony stimulating factor (∂ = 12.61, p = .052). Consistent with the study model and intervention design, significant changes observed 2 months post intervention indicated that TC may help down-regulate proinflammatory cytokines associated with underlying CVD risk, including interferon gamma (∂ = 149.90, p = .002), tumor necrosis factor (∂ = 16.78, p = .002), interleukin (IL) 8 (∂ = 6.47, p = .026), and IL-4 (∂ = 2.13, p = .001), and may increase mindfulness (∂ = .54, p = .021), spiritual thoughts and behaviors (∂ = 8.30, p = .009), and self-compassion (∂ = .44, p = .045). Conclusion. This study contributes important insights into the potential benefits and mechanisms of TC and, with further research, may ultimately lead to effective strategies for reducing CVD risk in women earlier in the CVD trajectory.